Analysing the AD process: creativity, accuracy and experience - Ramos, Marina; Rojo, Ana (The Journal of Specialised Translation, 2020)
The study of audio description (AD) has flourished over the last decade to become a broad research area in its own right. However, experimental research on the processes involved in the creation of AD is still scarce. More specifically, the study of describers’ psychological traits has so far been a rather unexplored area in the field. The present study focuses on creativity as one of the main professional competencies required for AD. In order to study the relationship between creativity, accuracy and experience, we recruited 10 professional describers and measured their creativity through a validated creativity test. They were then asked to create AD scripts for four highly poetic scenes. Their performance was analysed in terms of the accuracy and subjectivity of the texts. Our results show that more experienced describers are more creative, less subjective and more accurate when creating their descriptions.